Efektivitas Penggunaan Flashcard Bergambar terhadap Penguasaan Mufradat Bahasa Arab pada Siswa SMP - Siti Sarah; Yeni Nuriah Fitri (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Vocabulary (mufradat) mastery is a fundamental competence that determines success in Arabic language learning. However, many students still experience difficulties in understanding and retaining vocabulary due to the use of instructional media that does not adequately support the learning process. This study aimed to analyze the effectiveness of picture flashcards in improving Arabic vocabulary mastery among eighth-grade students at SMP Al Anwar. A quantitative approach employing a pre-experimental One Group Pretest–Posttest Design was adopted. The participants consisted of 26 students selected through total sampling. Data were collected using pretest and posttest instruments as well as documentation, and were analyzed using descriptive statistics and a paired sample t-test. The findings revealed that the students’ mean score increased from 59.42 in the pretest to 82.15 in the posttest. Hypothesis testing indicated a statistically significant difference in students’ Arabic vocabulary mastery before and after learning with picture flashcards. These findings demonstrate that picture flashcards are effective in enhancing Arabic vocabulary mastery by strengthening vocabulary comprehension, improving memory retention, and encouraging students’ active engagement throughout the learning process.